Effects of canagliflozin on kidney oxygenation evaluated using blood oxygenation level-dependent MRI in patients with type 2 diabetes - Mori, Katsuhito; Inoue, Tsutomu; Machiba, Yuri; Uedono, Hideki; Nakatani, Shinya; Ishikawa, Masahiro; Taniuchi, Satsuki; Katayama, Yutaka; Yamamoto, Akira; Kobayashi, Naoki; Kozawa, Eito; Shimono, Taro; et al. (Frontiers in Endocrinology, 2024)
Background: Recent clinical studies suggest protective effects of SGLT2 inhibitors on kidney disease outcome. Chronic hypoxia has a critical role in kidney disease development, thus we speculated that canagliflozin, an SGLT2 inhibitor, can improve kidney oxygenation. Methods: A single-arm study was conducted to investigate the effects of canagliflozin on T2* value, which reflects oxygenation level, in patients with type 2 diabetes (T2D) using repeated blood oxygenation level-dependent MRI (BOLD MRI) examinations. Changes in cortical T2* from before (Day 0) to after single-dose treatment (Day 1) and after five consecutive treatments (Day 5) were evaluated using 12-layer concentric objects (TLCO) and region of interest (ROI) methods.Results: In the full analysis set (n=14 patients), the TLCO method showed no change of T2* with canagliflozin treatment, whereas the ROI method found that cortical T2* was significantly increased on Day 1 but not on Day 5. Sensitivity analysis using TLCO in 13 well-measured patients showed that canagliflozin significantly increased T2* on Day 1 with no change on Day 5, whereas a significant improvement in cortical T2* following canagliflozin treatment was found on both Day 1 and 5 using ROI.Conclusions: Short-term canagliflozin treatment may improve cortical oxygenation and lead to better kidney outcomes in patients with T2D.